HEART AND LUNG FAILURE, TRANSPLANTOLOGYDoes the postoperative troponin I blood concentration measured in the perioperative period influence hemodynamic function of a transplanted heart? - Wierzbicki, Karol; Bochenek, Maciej; Kędziora, Anna; Sojecki, Krzysztof; Ciołczyk-Wierzbicka, Dorota; Węgrzyn, Piotr; Drwiła, Rafał; Kapelak, Bogusław; Milaniak, Irena; Sadowski, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction: Plasma troponin I (TnI) concentration is a well-established and widely-used marker of myocardial damage. Aim: To determine the correlation between TnI concentration measured within the first 4 days following heart transplantation (HTX) and clinical course, with consideration of hemodynamic performance. Material and methods: The retrospective study included 54 patients (12-62 years) who underwent HTX. TnI levels were assessed over the first 4 post-operative days. Hemodynamic parameters were assessed daily at Swan-Ganz catheterization and echocardiography. The number of required inotropic drugs was also analyzed. Results: There is a strong and positive correlation between the mean TnI levels and the mean number of required inotropic drugs (r = 0.51, p = 0.00), and also mean central venous pressure (CVP) (r = 0.33, p = 0.015). A weak trend towards a positive correlation between the mean values of pulmonary capillary wedge pressure (PCWP) and the mean plasma TnI levels was observed. There was no correlation between mean TnI levels and mean values of ejection fraction (EF) and cardiac output (CO). Detailed analysis showed a statistically significant correlation between TnI levels on days 3 and 4 after HTX and PCWP on the preceding days (r = 0.32, p = 0.04; r = 0.46, p = 0.006 respectively). Furthermore, a strong, inverse correlation between TnI levels on day 3 and CO on day 4 following HTX was observed (r = –0.44, p = 0.03). Conclusions: Plasma TnI could be a useful marker for assessing the hemodynamic function after HTX.